Functional Outcome of Titanium Elastic Nail Fixation in Diaphyseal Fractures of Forearm in Adolescents - Kandel, Krishna; Dhungana, Milan; Poudel, Dipesh; Shrestha, Bikram Prasad; Baral, Pramod; Shah, Jitendra; Lamichhane, Sameer (Nepal Orthopaedic Association Journal, 2023)
Introduction: This study aims to assess the functional outcomes of Titanium Elastic Nailing System (TENS) fixation for managing diaphyseal forearm fractures in adolescents. Method: The study was a prospective clinical study conducted at B.P. Koirala Institute of Health Sciences Between December 1, 2020, and November 30, 2021. Ethical clearance was obtained from the Institutional Review Committee (Registration Number 305/077/078-IRC). A total of 27 patients who underwent TENS fixation for forearm diaphyseal fractures were included. Patients were followed at 2 weeks, 6 weeks, 12 weeks, and 24 weeks. Radiological and functional outcome evaluations were assessed, including the range of motion, deformity, and time taken for union and active recovery. Collected data were entered in Microsoft Excel and converted to SPSS (Statistical Package for Social Sciences) version 28 for statistical analysis. Results: Among 27 included patients, 66.7% were males, 81.5% were within the age group of 10-13 years, 70.4% fell on outstretched hands, and 66.7% had fractures at the middle third of the forearm. Union was seen in 6 weeks among 29.6%, 12 weeks among 66.6%, and 24 weeks among 3.8%—7.4% developed complications. Conclusion: TENS is an effective fixation method for diaphyseal forearm fractures in adolescents and provides satisfactory functional outcomes.